Cis-Regulatory Elements Determine Germline Specificity and Expression Level of an Isopentenyltransferase Gene in Sperm Cells of Arabidopsis . Issue 3 (6th January 2016) - Zhang, Jinghua; Yuan, Tong; Duan, Xiaomeng; Wei, Xiaoping; Shi, Tao; Li, Jia; Russell, Scott D.; Gou, Xiaoping
Abstract : A regulatory region consisting of duplicated motifs activates gene expression in plant male gamete. Abstract: Flowering plant sperm cells transcribe a divergent and complex complement of genes. To examine promoter function, we chose an isopentenyltransferase gene known as PzIPT1 . This gene is highly selectively transcribed in one sperm cell morphotype of Plumbago zeylanica, which preferentially fuses with the central cell during fertilization and is thus a founding cell of the primary endosperm. In transgenic Arabidopsis ( Arabidopsis thaliana ), PzIPT1 promoter displays activity in both sperm cells and upon progressive promoter truncation from the 5′-end results in a progressive decrease in reporter production, consistent with occurrence of multiple enhancer sites. Cytokinin-dependent protein binding motifs are identified in the promoter sequence, which respond with stimulation by cytokinin. Expression of PzIPT1 promoter in sperm cells confers specificity independently of previously reported Germline Restrictive Silencer Factor binding sequence. Instead, a cis-acting regulatory region consisting of two duplicated 6-bp Male Gamete Selective Activation (MGSA ) motifs occurs near the site of transcription initiation. Disruption of this sequence-specific site inactivates expression of a GFP reporter gene in sperm cells. Multiple copies of the MGSA motif fused with the minimal CaMV35S promoter elements confer reporter gene expression in sperm cells. Similar duplicated MGSA motifs are also identified from promoter sequences of sperm cell-expressed genes in Arabidopsis, suggesting selective activation is possibly a common mechanism for regulation of gene expression in sperm cells of flowering plants.